Abductive Reasoning: Challenges Ahead - Atocha Aliseda (Theoria, 2009)
The purpose of this piece is to provide a critical analysis on some key aspects of abduction, as conceived by several researchers through my book Abductive Reasoning. These contributions raise fundamental questions concerning the conjectural character of abduction, its psychological status, its logical and computational structure as well as its role as inference to the best explanation and as a process of epistemic change.